2022
DOI: 10.1039/d2ra02864f
|View full text |Cite
|
Sign up to set email alerts
|

Recent update on electrospinning and electrospun nanofibers: current trends and their applications

Abstract: Electrospinning is a versatile and viable technique for generating ultrathin fibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(42 citation statements)
references
References 131 publications
0
42
0
Order By: Relevance
“…Synthetic polymer-based spinning membranes, including polycaprolactone (PCL), poly(lactic-co-glycolic acid) (PLGA), and polyethylene glycol (PEG), are thin, exible, and biocompatible [46] . These membranes can be readily produced using a range of spinning techniques, including electrospinning, solution spinning, and melt spinning [47] . In our study, the PLLA/HA@Irisin nano bers demonstrated exceptional mechanical characteristics, including elevated tensile strength and exibility, rendering it an optimal candidate for bone tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic polymer-based spinning membranes, including polycaprolactone (PCL), poly(lactic-co-glycolic acid) (PLGA), and polyethylene glycol (PEG), are thin, exible, and biocompatible [46] . These membranes can be readily produced using a range of spinning techniques, including electrospinning, solution spinning, and melt spinning [47] . In our study, the PLLA/HA@Irisin nano bers demonstrated exceptional mechanical characteristics, including elevated tensile strength and exibility, rendering it an optimal candidate for bone tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…In this method, the biomaterial under construction into nanofibers (e.g., polymers) is synthesized inside the holes of a template membrane with uniformly sized orifices. This technique allows the synthesis of nanofibers with varying diameters, and this is usually achieved by changing the template settings [ 88 ]. The fabrication of nanofibrous scaffolds for skin tissue engineering using a template-assisted electrospinning technique was employed in the production of structural scaffolds with the use of polycaprolactone.…”
Section: Commonly Employed Manufacturing Techniquesmentioning
confidence: 99%
“…Under the influence of external electrostatic fields, electrospinning technology, a sophisticated technique for fiber production, rapidly stretches polymers into continuous fibers with sizes varying from microns to nanometers [ 1 , 2 , 3 ]. Electrospinning technology has several advantages over other fiber film production techniques, including ease of operation, controllable process, high operability, low cost, and flexibility.…”
Section: Introductionmentioning
confidence: 99%